"Filozofia medie". Studiul concepţiilor despre fericire şi iubire prin anchete sociologice cantitative - Cosima Rughiniș (Sociologie Românească, 2007)
The article explores the possibility to analyse common life philosophies through quantitative sociological surveys. Two such surveys are used to see whether people’s conceptions about hardship and happiness, and about marriage and happiness, seem to be generally valid in the population, and how they are influenced by one’s own life experiences. The analysis suggests that these common theories are good descriptions of the social reality – with two significant exceptions regarding religious faith and poverty. Connections between experience and life philosophies may be twofold: compensatory and moralizing. The former underestimates the importance of a given factor in influencing happiness, while the latter overestimates it.